Incidence and treatment of arrhythmias secondary to coronavirus infection in humans: A systematic review. (26th November 2020) - Malaty, Michael; Kayes, Tahrima; Amarasekera, Anjalee T; Kodsi, Matthew; MacIntyre, C Raina; Tan, Timothy C
Abstract: Background: The coronavirus disease 2019 (COVID‐19) pandemic has affected millions of people worldwide resulting in significant morbidity and mortality. Arrhythmias are prevalent and reportedly, the second most common complication. Several mechanistic pathways are proposed to explain the pro‐arrhythmic effects of severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) infection. A number of treatment approaches have been trialled, each with its inherent unique challenges. This rapid systematic review aimed to examine the current incidence and available treatment of arrhythmias in COVID‐19, as well as barriers to implementation. Methods: Our search of scientific databases identified relevant published studies from 1 January 2000 until 1 June 2020. We also searched Google Scholar for grey literature. We identified 1729 publications of which 1704 were excluded. Results: The incidence and nature of arrhythmias in the setting of COVID‐19 were poorly documented across studies. The cumulative incidence of arrhythmia across studies of hospitalised patients was 6.9%. Drug‐induced long QT syndrome secondary to antimalarial and antimicrobial therapy was a significant contributor to arrhythmia formation, with an incidence of 14.15%. Torsades de pointes (TdP) and sudden cardiac death (SCD) were reported. Treatment strategies aim to minimise this through risk stratification and regular monitoring of corrected QT interval (QTc). Conclusion: Patients with SARS‐CoV‐2 are at an increased risk of arrhythmias. Drug therapy is pro‐arrhythmogenic and may result in TdP and SCD in these patients. Risk assessment and regular QTc monitoring are imperative for safety during the treatment course. Further studies are needed to guide future decision‐making.